Effect of Particle Size on Material Recovery and Elemental Distribution in the Recycling of End-of-Life Polycrystalline Silicon Photovoltaic Modules - Albashir, Yasir; Islamiyat, Waheed; Ibrahim, Tahir; Mohammad, Ndagi; Sule, Erten Ela; Umar, Hauwa yahaya; S.M Gume (FUDMA Journal of Sciences, 2026)
The rapid deployment of photovoltaic (PV) systems has raised concerns regarding the management of end-of-life (EoL) solar modules. This study investigates the recovery efficiency of polycrystalline silicon PV panels subjected to sequential mechanical and thermal treatments, with emphasis on the influence of particle size distribution on downstream chemical and structural characterization. Disassembled PV modules (≈2 kg per test) were crushed using mortar-and-pestle and hammer-impact methods, followed by sieving into coarse (>5 mm), medium (1–5 mm), and fine (0.08–0.40 mm) fractions. Thermal treatment at 650 °C facilitated the removal of encapsulant materials, after which the recovered fractions were characterized using X-ray diffraction (XRD) and X-ray fluorescence (XRF) analyses. Results indicated improved recovery efficiency in finer fractions, with glass yields increasing from 71.3% in the coarse fraction to 83.4% in the fine fraction. XRD analysis revealed dominant phases of quartz (SiO₂), albite (NaAlSi₃O₈), and lime (CaO), while XRF analysis confirmed enrichment of silicon (Si) and antimony (Sb) in finer fractions. Statistical analysis using one-way ANOVA (p < 0.05) showed significant differences among particle size fractions in terms of recovery yield and elemental composition, indicating the practical importance of particle size optimization in PV recycling processes. The findings demonstrate that particle size engineering plays a critical role in improving material recovery efficiency and supports the development of sustainable circular photovoltaic recycling strategies.  This study investigates the recovery efficiency of polycrystalline silicon PV panels subjected to sequential mechanical and thermal treatments, with emphasis on the influence of particle size distribution on downstream chemical.
Keywords: Photovoltaic waste; particle size distribution; Recycling; material recovery; circular photovoltaics